Unstuck Technology for EPB/TBM Dual Mode Shield Machine Stuck in Rock Stratum - DUAN Yueqiang (Chengshi guidao jiaotong yanjiu)
［Objective］ During the tunneling process of the EPB (earth pressure balance shield machine)/TBM (full-face hard rock tunnel boring machine) dual-mode shield tunneling machine, problems such as excessive wear of the cutting tools and improper setting of tunneling parameters are prone to cause accidents like jamming, which will further seriously affect the construction period and even lead to safety accidents. Therefore, it is necessary to conduct research on the unstuck technology of the EPB/TBM dual-mode shield tunneling machine from jamming during hard rock tunneling. ［Method］ In the Dameisha Station- Xiaomeisha Station tunnel of the Construction Area 3, Phase II project on Shenzhen Metro Line 8, based on the whole process of the jamming accident of the EPB/TBM dual-mode shield tunneling machine during the full-face slightly weathered hard rock tunneling, the process of the EPB/TBM dual-mode shield tunneling machine unstuck from jamming is systematically elaborated, and the evolution law of the tunneling parameters from jamming to unstuck is analyzed. Then the causes of the jamming accidents are summarized, and corresponding preventive measures and suggestions are put forward. ［Result & Conclusion］ The jamming of shield tunneling machine is mainly caused by the combined effects of multiple factors, among which the abnormal wear of the cutter head and cutting tools is one of the core reasons. By promptly investigating the abnormal changes in relevant tunneling parameters, such as sudden drops in the tunneling speed of the shield machine, or in the torque of the cutter head, and a significant increase in the total thrust force, the occurrence of jamming can be predicted in advance or even avoided. A comprehensive judgment of the muck accumulation in the cutter head and the earth chamber during investigation can significantly reduce the occurrence of jamming and prevent it from further aggravating. Successful escaping can be achieved through procedures such as determining the jamming position of the shield tunneling machine, breaking through the rock mass of the cutting ring, welding the jacking and bracing fixtures, conducting a trial propulsion of the shield tunneling machine, cutting the first part of the shield body and breaking through the rock mass, cutting the second part of the shield body and breaking through the rock mass, in-situ welding of the cut shield body, and resuming the tunneling of the shield tunneling machine